Responding to food insecurity: Employing the market information and food insecurity response analysis framework in rural northern Kenya - Mude, Andrew G.; Ouma, R.; Lentz, Erin C. (Informa UK Limited, 2012)
Aid agencies are increasingly advocating for cash transfers as a substitute or complement to food transfers when responding to both emergency and chronic food insecurity. Yet, cash is not always optimal. In this article, we demonstrate how a newly developed response analysis tool, the Marketing Information and Food Insecurity Response Analysis (MIFIRA) framework can guide evidence-based identification of appropriate transfers. We present findings from a MIFIRA analysis in Marsabit; a remote and generally food-insecure district of northern Kenya. As a demonstration of the analytical versatility of MIFIRA, we utilise a variety of data, ranging from rigorously-collected household data, to market surveys and rapid assessments in focus groups. As a proof of concept, this article shows how MIFIRA can be effectively deployed in other regions facing chronic or emergency food insecurity to help response agencies make systematic decisions on a solid evidence base.